2014
DOI: 10.1159/000369454
|View full text |Cite
|
Sign up to set email alerts
|

Angelman Syndrome: A Case Series Assessing Neurological Issues in Adulthood

Abstract: Background: This study aimed to evaluate the clinical symptoms of Angelman syndrome (AS) in adults and to identify the neurological pathways affected in this disease. AS is a neurogenetic disorder resulting due to the deletion or inactivation of the ubiquitin-protein-ligase E3A gene on maternal chromosome 15. Summary: A retrospective analysis of data from six adults patients with clinical, electroencephalographic and genetic confirmation of AS was performed. Movement disorders of the hands and mouth, laughing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Several studies in AS reported severe seizures in early childhood with a distinct improvement during later childhood [61][62][63]. Seizure remission in late teens and early twenties followed by recurrence of seizures in third or fourth decades has been reported [64].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in AS reported severe seizures in early childhood with a distinct improvement during later childhood [61][62][63]. Seizure remission in late teens and early twenties followed by recurrence of seizures in third or fourth decades has been reported [64].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and other behavioral issues can have a significant impact on quality of life for adults with AS. Although, behavioral issues appear to decrease with age, anxiety becomes significantly more prevalent (Giroud et al, ; Larson et al, ; Thibert et al, ). In this cohort, 57% had a history of anxiety symptoms that impact day‐to‐day function and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…As the first generations of individuals diagnosed with AS in childhood are now aging into adulthood, we are continuing to learn how to optimize their care. To date, there have been multiple case reports characterizing AS in adulthood (Buntinx et al, ; Clayton‐Smith, ; Giroud et al, ; Laan et al, ; Larson et al, ; Sandanam et al, ). We completed a large interview series with caregivers in 2015 to help characterize the impact of age and genotype on clinical outcomes for adolescents and adults with AS (Larson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Far less is known is about the course of the syndrome in adulthood. Only a limited number of studies described the course of the AS in adults (Buckley, Dinno, & Weber, 1998;Clayton-Smith, 1993;Giroud et al, 2015;Guerrini et al, 1996;Jacobsen et al, 1998;L. A. E. M. Laan, Den Boer, Hennekam, Renier, & Brouwer, 1996;Leitner & Smith, 1996;Minassian et al, 1998;Moncla et al, 1999;Penner, Johnston, Faircloth, Irish, & Williams, 1993;Sandanam et al, 1997;Williams & Frias, 1982;Williams, Gray, Hendrickson, Stone, & Cantu, 1989).…”
mentioning
confidence: 99%